Probiotic Therapy as a Novel Approach for Allergic Disease - Toh, Zheng Quan; Anzela, Anzela; Tang, Mimi L.; Licciardi, Paul V. (Frontiers in Pharmacology, 2012)
The prevalence of allergic disease has increased dramatically in Western countries over the past few decades. The hygiene hypothesis, whereby reduced exposure to microbial stimuli in early life programs the immune system towards a Th2-type allergic response, is suggested to be a major mechanism to explain this phenomenon in developed populations. Such microbial exposures are recognised to be critical regulators of intestinal microbiota development. Furthermore, intestinal microbiota has an important role in signalling to the developing mucosal immune system. Intestinal dysbiosis has been shown to precede the onset of clinical allergy, possibly through altered immune regulation. Existing treatments for allergic diseases such as eczema, asthma and food allergy are limited and so the focus has been to identify alternative treatment or preventive strategies. Over the past 10 years, a number of clinical studies have investigated the potential of probiotic bacteria to ameliorate the pathological features of allergic disease. This novel approach has stemmed from numerous data reporting the pleiotropic effects of probiotics that include immunomodulation, restoration of intestinal dysbiosis as well as maintaining epithelial barrier integrity. In this mini-review, the emerging role of probiotics in the prevention and/or treatment of allergic disease are discussed with a focus on the evidence from animal and human studies.